Analytical Capabilities of Financial Reporting and Its Relationship with Managerial Reporting - Ometsinska, Iryna; Ometsinskyi, Orest (Herald of Economics, 2025)
Introduction. The Ukrainian economy is currently experiencing a challenging period, which has affected business operations, with many enterprises having gone bankrupt or being on the verge of insolvency. To find ways out of the crisis, businesses must make effective management decisions aimed at identifying weaknesses in their operations, responding promptly to external changes, and increasing investment attractiveness. This requires the establishment of a reliable information support system for management, in which financial reporting and its analytical functions play a key role. A high-quality financial statement analysis provides valuable information that enables external users to make investment and other decisions regarding collaboration with a company, while internal users can identify operational issues and growth prospects. Since internal users of financial statements have access to management reporting, combining the analytical capabilities of both reports enhances the informational function of accounting and financial analysis systems.Purpose. The aim of this study is to explore ways to develop and strengthen the analytical capabilities of financial reporting through its integration with management reporting, thereby enabling users to make well-informed management decisions within the limits of available information.Methods. To achieve the research objective, the following methods were used: comparison, trend analysis, and grouping to examine the efficiency of Ukrainian enterprises; systemic, abstract-logical, inductive, and deductive methods to outline the requirements for the system of indicators used in financial statement analysis; analogy, analysis, and synthesis to identify the benefits of integrating financial and management reporting for managerial analysis; as well as ratio analysis, modeling, and analogy to improve the methodology for assessing a company’s liquidity and profitability.Results. The study proves the necessity of conducting a comprehensive analysis of financial statements (for both external and internal users) in combination with management reporting (for internal users), which contributes to the formation of a high-quality information environment for making well-informed management decisions. The research identifies key requirements for a financial statement analysis system, including comprehensiveness, structure, user orientation, timeliness, clarity, and comparability. It highlights the importance of ensuring that analytical indicators meet the comparability criterion and identifies barriers to comparability, such as changes in accounting methods, adjustments to accounting estimates, inflationary processes, and differences in reporting approaches under National Accounting Standards and International Financial Reporting Standards. The study also outlines the advantages of integrating financial and management reporting for managerial analysis. Furthermore, the methodology for liquidity analysis has been enhanced through improvements in the calculation of the absolute liquidity ratio, while profitability analysis has been refined by introducing additional indicators such as «operating profitability» and «profitability of products» broken down by product types.Prospects for further research. Future research should focus on grouping financial statement analysis indicators and exploring their informational value for different users to develop a high-quality analytical system for decision-making.